Pengaruh pemberian antibiotika saat budidaya terhadap keberadaan residu pada daging dan hati ayam pedaging dari peternakan rakyat - Nina Marlina A; Elok Zubaidah; Aji Sutrisno (Jurnal Ilmu-Ilmu Peternakan (Indonesian Journal of Animal Science), 2015)
The use of antibiotics in animal husbandry cannot be avoided either as an act of therapy, supportive or prevention. This study was aimed to determine the existence of antibiotic residues in broiler chicken products which were produced by poultry farm and to determine the safety level of residues in the product which was associated with a drug application and harvesting time. Thigh meat and liver samples of broiler were taken when thinning and harvesting time in poultry farm at Pamijahan- Bogor using purposive sampling method. Residue testing was conducted through bioassay screening test. Positive results were followed by a confirmatory test using HPLC. Total positive samples were detected residues reached 27.08% which included the macrolide group reached 22.92% and tetracycline group reached 4.17%. These residues were found in the liver, reaching 50% of the total sample of the liver. In addition, 53.85% of the positive samples came from broiler chicken samples taken during thinning period. Macrolide antibiotics in liver samples were detected in the form of erythromycin with the level compounds between 0085 - 0702 ppm. Moreover, 90.9% of the samples had levels exceeding MRL defined in SNI 01-6366-2000 and CAC/MRL-2-2012. Tetracycline antibiotic was detected in the form of doxycycline with the level compounds between 0-0067 ppm on thigh meat and 0-0085 ppm in the liver although these levels were still below the MRL. The residues existence was closely related to the drug dose and farmer’s knowledge about withdrawal time. Keyword: antibiotic, residue, broiler, drug dose,harvesting time